2019
DOI: 10.26434/chemrxiv.9108461.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AdBippyPhos Promotes Pd-Catalyzed C–N Coupling Between Weakly Nucleophilic Sulfonamides and Heteroaryl Halides

Abstract: Sulfonamides are poor nucleophiles in Pd C-N coupling catalysis, hindering synthesis of densely-functionalized N,N-diaryl sulfonamide motifs relevant to medicinal chemistry. Through targeted high-throughput experimentation (HTE), we have identified the Pd/AdBippyPhos catalyst system as an effective and general method to construct this difficult to access moiety. In particular, AdBippyPhos is critical for the installation of heteroaromatic groups. Computational steric parameterization of the investigated ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In 2019 we, along with collaborators at GSK and Temple University, conducted a similar study of a challenging C-N coupling involving sulfonamide arylation. 89 Multi-substrate HTE revealed the BippyPhos class of ligands as superior, with AdBippyPhos as the optimal candidate.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019 we, along with collaborators at GSK and Temple University, conducted a similar study of a challenging C-N coupling involving sulfonamide arylation. 89 Multi-substrate HTE revealed the BippyPhos class of ligands as superior, with AdBippyPhos as the optimal candidate.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 undergraduate teaching lab experiments on microscale HTE employ Pd-catalyzed reactions as the exemplars. 88 Our research group focuses not only using HTE and data-rich techniques to develop new reactions, [89][90][91][92][93] but also to better understand how reactivity and mechanism change as a function of the reaction system. 41,94,95 To enable these efforts in the realm of organopalladium chemistry, we identified a need for Pd precursor compounds that are specifically suited to HTE studies.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
“…More recently, Stradiotto and co‐workers reported use of BippyPhos/[Pd(cinnamyl)Cl] 2 for arylation of amides and sulfonamides with K 2 CO 3 as base . A related study by GSK showed that AdBippyPhos ( 16 ) was optimal for the coupling of sulfonamides with heteroaryl halides …”
Section: Discovery and Development Of Bippyphosmentioning
confidence: 99%
“…We propose that the success of L6 is related to specific steric properties, as evidenced by the large ECA and G­(Pd) determined through the steric modeling of Pd–phosphine complexes. This interplay of ligand cone angle and G­(Pd) provide a set of criteria for evaluating new potential ligand scaffolds for sulfonamide arylations; work to test this hypothesis is currently underway …”
mentioning
confidence: 99%